Development and evolution of tooth renewal in neoselachian sharks as a model for transformation in chondrichthyan dentitions - Meredith Smith, Moya (J Anat, 2018)
A defining feature of dentitions in modern sharks and rays is the regulated pattern order that generates multiple replacement teeth. These are arranged in labio‐lingual files of replacement teeth that form in sequential time order both along the jaw and within successively initiated teeth in a deep dental lamina. Two distinct adult dentitions have been described: alternate, in which timing of new teeth alternates between two adjacent files, each erupting separately, and the other arranged as single files, where teeth of each file are timed to erupt together, in some taxa facilitating similarly timed teeth to join to form a cutting blade. Both are dependent on spatiotemporally regulated formation of new teeth. The adult Angel shark Squatina (Squalomorphii) exemplifies a single file dentition, but we obtained new data on the developmental order of teeth in the files of Squatina embryos, showing alternate timing of tooth initiation. This was based on micro‐CT scans revealing that the earliest mineralised teeth at the jaw margin and their replacements in file pairs (odd and even jaw positions) alternate in their initiation timing. Along with Squatina, new observations from other squalomorphs such as Hexanchus and Chlamydoselachus, together with representatives of the sister group Galeomorphii, have established that the alternate tooth pattern (initiation time and replacement order) characterises the embryonic dentition of extant sharks; however, this can change in adults. These character states were plotted onto a recent phylogeny, demonstrating that the Squalomorphii show considerable plasticity of dental development. We propose a developmental‐evolutionary model to allow change from the alternate to a single file alignment of replacement teeth. This establishes new dental morphologies in adult sharks from inherited alternate order.